Stereotactic Body Radiotherapy Using Cyberknife for Localized Prostate Cancer - Kim, Hunjung; Phak, Hoonjung; Kim, Woochul (Reports of Radiotherapy and Oncology, 2015)
Background: Stereotactic body radiation therapy (SBRT) using Cyberknife delivers high-dose fraction of radiation without increasing toxicity. Objectives: We present the follow-up outcomes and toxicities of patients with localized prostate cancer treated by use of Cyberknife as a monotherapy. Patients and Methods: This study was based on a retrospective analysis of the 34 patients treated with SBRT using Cyberknife for localized prostate cancer (26.5% low risk, 67.6% intermediate risk, and 5.9% high risk). Total dose of 36.25 Gy in 5 fractions of 7.25Gy were administered without use of androgen deprivation therapy (ADT). The acute and late toxicities were recorded using the radiation therapy oncology group scale. Prostate-specific antigen (PSA) response was monitored. Results: Thirty-four patients with a median 52 months (range 12 - 71 month) follow-up were analyzed. The biochemical relapse-free survival was 93.3%. PSA fell to a median of 0.39 ng/mL at 4 years and PSA bounce occurred in 28.1% of patients. Acute side effects resolved within 1 - 2 months of treatment completion. There was no grade 3 and 4 late toxicity observed. Conclusions: In this study, SBRT using Cyberknife without ADT has provided promising outcomes in localized prostate cancer with good PSA response and minimal toxicity. Hypofractionated SBRT using Cyberknife leads to long-term favorable 5-year biochemical relapse-free survival and minimal toxicity in localized prostate cancer as a monotherapy.